Land Use for Renewable Energy Power Plant and the Impact of CO2 Emission: An Indonesian Case Study - Priambodo, Nur Widi; Raharjo, Jangkung; Rokhmat, Mamat (International Journal of Energy Economics and Policy, 2022)
The energy crisis, global warming, emissions, and greenhouse gas effects have become a global issue and an urgent problem to be resolved. CO2 is One of the contributors to global warming. The operation of fossil energy generation produces CO2 significantly. This paper examines the use of land for renewable energy power plant and the impact. The operation of 648 MW renewable energy power plants can reduce CO2 emissions by 94.78% compared to the coal-fired power plants at the same capacity. However, the construction of renewable energy plants requires a much larger area, which is 44.89 to 78.51 times the land requirement for coal-fired power plants. So, land clearing for renewable energy power plants will result in a much larger loss of land absorption for CO2 emissions compared to coal-fired power plants. The use of plantation land can reduce CO2 emissions due to the total operation and clearing of land of 4,444,907.97 tons/year up to 4,452,016.56 tons/year compared to the construction of the coal-fired power plant, at the same capacity. The use of plantation land for the construction of renewable energy power plant reduces the impact of CO2 emissions by up to 95.39% compared to the construction and operation of the coal-fired power plants.